Discrete simulations of spatio-temporal dynamics of small water bodies under varied stream flow discharges - Sagar, , BSD (2005)
Spatio-temporal patterns of small water bodies (SWBs) under the influence of temporally varied stream flow discharge are simulated in discrete space by employing geomorphologically realistic expansion and contraction transformations. Cascades of expansion-contraction are systematically performed by synchronizing them with stream flow discharge simulated via the logistic map. Templates with definite characteristic information are defined from stream flow discharge pattern as the basis to model the spatio-temporal organization of randomly situated surface water bodies of various sizes and shapes. These spatio-temporal patterns under varied parameters (lambda s) controlling stream flow discharge patterns are characterized by estimating their fractal dimensions. At various lambda s, nonlinear control parameters, we show the union of boundaries of water bodies that traverse the water body and non-water body spaces as geomorphic attractors. The computed fractal dimensions of these attractors are 1.58, 1.53, 1.78, 1.76, 1.84, and 1.90, respectively, at lambda s of 1, 2, 3, 3.46, 3.57, and 3.99. These values are in line with general visual observations.